Answer:
1. Solving for y in the first equation, y = 0
2. Substituting 0 in for y in the second equation
3. A zero is in the denominator which is undefined
4. Therefore, the result is no solution.
Step-by-step explanation
To solve the equation by substitution, we need to solve the first equation by y and replace the expression on the second equation.
So, if we decide to solve for y, we will get:
y + 2x = 2x
y + 2x - 2x = 2x - 2x
y = 0
There replacing y = 0 on the second equation:
4x/7(0) = 8
4x/0 = 8
Since we can divide by 0, the system has no solution.
Therefore, the order of the steps are:
1. Solving for y in the first equation, y = 0
2. Substituting 0 in for y in the second equation
3. A zero is in the denominator which is undefined
4. Therefore, the result is no solution.